Visual Acuity, Retinal Sensitivity, and Macular Thickness Changes in Diabetic Patients without Diabetic Retinopathy after Cataract Surgery - Spela Stunf Pukl; Nataša Vidović Valentinčič; Mojca Urbančič; Irena Irman Grčar; Rok Grčar; Vladimir Pfeifer; Mojca Globočnik Petrovič (Journal of Diabetes Research)
Aim. Functional and morphological macular study after cataract surgery in a group of diabetics without diabetic retinopathy compared to nondiabetics to evaluate the effect of surgical oxidative stress on diabetic retina. Methods. Prospective, comparative study. Preoperative eye exam, best corrected visual acuity (BCVA) measured by ETDRS letters, and optical coherence tomography (OCT) were followed by standard cataract surgery. The follow-up visits at 1, 3, and 6 months postoperatively included BCVA, OCT, and microperimetry, to analyze changes within and between the groups. Results. The BCVA improved significantly in diabetics and controls: 64.2 to 81.0 and 61.9 to 82.1 ETDRS at 6 months, respectively. The central macula at OCT significantly thickened in both groups, while the central 5 fields, corresponding to the microperimetry area, subclinically thickened from 284.20 to 291.18 μm at 6 months only in diabetics (p=0.026). A matching slight decrease in the microperimetry sensitivity from 1 to 6 months was found also only in diabetics, with mean average difference −0.75 dB (p=0.04). Conclusion. Underlying diabetes does not influence the surgical outcome in diabetics without diabetic retinopathy. However, slight thickening of wider macula and corresponding decrease in retinal sensitivity observed in diabetics 6 months postoperatively might influence visual function on long term.